2001
DOI: 10.1021/jp010092u
|View full text |Cite
|
Sign up to set email alerts
|

Piezo X-ray Absorption Spectroscopy for the Investigation of Solid-State Transformations in the Millisecond Range

Abstract: The piezo XAFS technique in combination with an in situ cell has been used for the investigation of fast solid-solid transformations with millisecond time resolution. The technique records X-ray absorption spectra (XAFS) in a continuous mode by making use of piezo tilt tables in the X-ray monochromator, which are actuated by an oscillatory high voltage. The application of this technique in the field of solid-state chemistry and catalysis is illustrated by investigations of the X-ray absorption near-edge struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 54 publications
(140 reference statements)
0
41
0
Order By: Relevance
“…methanol synthesis, steam reforming and for gas phase oxychlorination. QEXAFS studies on Cu/ZnO systems have been reported in detail previously and indicate that Cu(I) species are very short-living intermediates in many reactions [2,3]. In other cases Cu(I) is much more stable, especially if spinels can be formed [11,12].…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…methanol synthesis, steam reforming and for gas phase oxychlorination. QEXAFS studies on Cu/ZnO systems have been reported in detail previously and indicate that Cu(I) species are very short-living intermediates in many reactions [2,3]. In other cases Cu(I) is much more stable, especially if spinels can be formed [11,12].…”
Section: Introductionmentioning
confidence: 80%
“…Considering nano-sized particles it is even possible to measure surface structures in absorption mode under conditions where other surface sensitive methods cannot be applied since they require a vacuum and/or a flat surface. Thus the application of QEXAFS in catalysis is most interesting due to the possibility of studying the dynamic changes of a catalyst in situ under realistic conditions [1][2][3][4][5]. Since the setup of a QEXAFS experiment is equal to conventional EXAFS setups and thus nowadays rather simple, it provides an easy access to such experiments and has recently attracted more and more attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For round-shaped particles the reaction time τ can be calculated according to the formula: with the size of the particles R p . For an effective diffusion coefficient of 10 -6 -10 -8 m 2 /s, τ amounts to 20 ms to 2 s. This has important consequences for time resolved studies in heterogeneously catalyzed reactions: Both the QEXAFS and the DEXAFS technique allow monitoring of structural changes in the millisecond regime [6,7]. Considering the reduction of the CuO/ZnO catalyst and equation (1), we can conclude that a reaction faster than ≈ 1 ms may be hampered by internal diffusion or even external mass transport, even in the ideal case of a sieved catalyst.…”
Section: Figurementioning
confidence: 99%